Crabapple fruit extracts lower hypercholesterolaemia in high-fat diet-induced obese mice. (December 2016) - Li, Mingxia; Xue, Shuangjia; Tan, Si; Qin, Xiaoxiao; Gu, Ming; Wang, Dongshan; Zhang, Yu; Guo, Lu; Huang, Feisi; Yao, Yunchong; Zhou, Zhiqin; Fan, Shengjie; et al.
Highlights: Crabapple extracts lowered TC and LDL-c levels. Crabapple extracts elevated the mRNA and protein levels of CYP7A1 in mouse liver. Crabapple extracts displayed antioxidant activity. Abstract: Crabapples are used as food and for the treatment of diarrhoea, indigestion and other digestive diseases in China. The anti-hyperlipidaemic and anti-hyperglycaemic effects of the extracts were evaluated on high-fat diet-induced obese mice. We found that the extracts of five crabapple varieties lowered serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) levels, and decreased serum triglyceride (TG) contents and improved fasting glucose levels in the mice. All extracts notably elevated the mRNA expression and protein levels of cholesterol 7 alpha-hydroxylase (CYP7A1), the crucial enzyme for cholesterol homeostasis, in the mouse liver. The extracts also displayed strong antioxidant activity in vitro . To our knowledge, this is the first study to show that the crabapples could lower cholesterol levels. Our data suggest that crabapple may lower cholesterol through the enhancement of CYP7A1 function in liver, and crabapple may be used as nutraceuticals to prevent or treat hyperlipidaemia and other metabolic disorders.